PERANCANGAN BUKU TENTANG RUMAH TRADISIONAL MAJAPAHIT DENGAN TEKNIK AUGMENTED REALITY UNTUK MENGENALKAN SEJARAH BUDAYA LOKAL - Ibadurrokhman, Ibadurrokhman; Bahruddin, Muhammad; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2016)
Interest traditional home design book on Majapahit with augmented reality technique is to introduce the public about the cultural history of Majapahit heritage home in the form of a traditional home. The study was conducted with a qualitative method that is based on interviews, observation, documentation, and literature to support the design of a book about the traditional home of Majapahit. The data can be analyzed by several stages of data reduction, data presentation, and conclusion. Having analyzed the data found a design concept that is informative, in a large dictionary Indonesian informative mean to be told. The concept aims to be informative book that is designed to provide an overview to the public about the traditional home of Majapahit. Augmented reality techniques promoted expected to help draft informative because it is interactive, so that people can know the shape of traditional houses Majapahit from various viewpoints .. Results from the design book is expected that the public know more about the cultural historical heritage in the form of a traditional home Majapahit Majapahit already displaced by the times. Keywords: Book, traditional house Majapahit, Augmented reality, local culture.